On the Frontier Between Nucleophilic Aromatic Substitution and Catalysis. Issue 18 (15th April 2014) - Pichette Drapeau, Martin; Ollevier, Thierry; Taillefer, Marc
Abstract A study on the arylation of heteroatom nucleophiles by using activated haloarenes, with or without metal catalysts, is reported. A discussion concerning the involvement of traces of metals is presented, supported by an unexpected ''ligand'' effect in the absence of added metal catalysts. We believe that the frontier between nucleophilic aromatic substitution and catalysis will likely prove to be much harder to delimit than is generally thought.